ANALISIS KARAKTERISTIK DAN KEBUTUHAN RUANG PARKIR PADA AREAL PUSAT PERBELANJAAN SUZUYA MALL BANDA ACEH - Muhammad Isya; Cut Mutiawati; Handayani Handayani (JURNAL TEKNIK SIPIL, 2014)
Suzuya Mall Banda Aceh is one of the shopping center in the city of Banda Aceh. This mall is located onJln. Teuku Umar street. Daily activities of community cause the increasing of trip, including the attraction trip to this mall. However, the availabililty of parking space can not be accommodated by the mall, especially during the peak hours. The purpose of this study are to analyze the characteristics, capacity and demand parking of Suzuya mall.The results analysis of this study are showed: for motorcycles, peak hour vehicle arrival is on Saturday 20.00-21.00 pm at 285 veh/h with a volume of 1751 veh/day. The average length of the highest parking on Sundays at 0.96 h/veh. The highest accumulation on Sunday of 219 veh between 16:00-17:00 pm. The highest parking capacity on Thursday by 517 Unit Parking Space.